"I still think we've got mountains to climb": Evaluating the grassroots sport participation legacy of the London 2012 Paralympic Games for disabled people in England - Brown, C. S. (University of Kent, 2019)
This research is the first to comprehensively evaluate and critically appraise the effectiveness of the London 2012 Paralympic Games (LPG) on the grassroots sports participation of disabled people in England. The findings enable future organisers of the Paralympic Games to understand the limitations and scope of the 'legacy' the event can have on disabled people's sport participation. In-depth interviews with senior managers from 30 sport and non-sport organisations revealed the LPG had a short-term impact on sport participation. Most sports organisations and VSCs failed to leverage the LPG and thus failed to capitalise on the demand generated by the LPG. The main benefit of the LPG was the perceived catalytic impact on the development of the disability sport system. 538 voluntary sport clubs (VSCs) completed an online questionnaire about the impact of the LPG on disabled people's participation at VSCs from sports featured at the LPG. The LPG had minimal impact on mainstream VSCs, but was more successful for VSCs from disability-specific sports. In general, VSCs were constrained by their knowledge of disability and provision of sport for disabled people, as well as resources required for leveraging the LPG. Data from an online questionnaire of 81 non-active disabled people revealed systemic and social constraints to be more prohibitive to sports participation than constraints linked to the LPG. Systemic and social constraints included provision of sport participation, economic factors, organisations offering unsuitable sport participation opportunities, and access to sport participation opportunities. This research found the Paralympic Games to be an ineffective mechanism for directly increasing disabled people's sport participation. Instead of viewing the Paralympic Games as a catalyst for sport participation, stakeholders should leverage the Paralympic Games' potential to increase awareness and demand for sport participation. The Paralympic Games should complement, rather than replace, efforts to increase disabled people's sport participation.